2014
DOI: 10.1098/rstb.2013.0284
|View full text |Cite|
|
Sign up to set email alerts
|

How the mechanisms of long-term synaptic potentiation and depression serve experience-dependent plasticity in primary visual cortex

Abstract: Donald Hebb chose visual learning in primary visual cortex (V1) of the rodent to exemplify his theories of how the brain stores information through long-lasting homosynaptic plasticity. Here, we revisit V1 to consider roles for bidirectional ‘Hebbian’ plasticity in the modification of vision through experience. First, we discuss the consequences of monocular deprivation (MD) in the mouse, which have been studied by many laboratories over many years, and the evidence that synaptic depression of excitatory input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 111 publications
(206 reference statements)
3
121
0
Order By: Relevance
“…That said, experiments in rodents [87] have isolated the binocular lateral geniculate nucleus inputs to layer 4 cells and have shown that the classic properties of ocular dominance plasticity exist at these synapses [88][89][90], which thus form the most straightforward testbed for understanding the synaptic mechanisms that underlie a behaviourally relevant form of plasticity. There seems to be general agreement that the initial weakening of the deprived eye depends on homosynaptic LTD [91]. Several types of experiments have demonstrated that biochemical alterations that block LTD in slice experiments can block the downregulation of the V1 response to the deprived eye.…”
Section: (B) Feedback Inhibitionmentioning
confidence: 94%
“…That said, experiments in rodents [87] have isolated the binocular lateral geniculate nucleus inputs to layer 4 cells and have shown that the classic properties of ocular dominance plasticity exist at these synapses [88][89][90], which thus form the most straightforward testbed for understanding the synaptic mechanisms that underlie a behaviourally relevant form of plasticity. There seems to be general agreement that the initial weakening of the deprived eye depends on homosynaptic LTD [91]. Several types of experiments have demonstrated that biochemical alterations that block LTD in slice experiments can block the downregulation of the V1 response to the deprived eye.…”
Section: (B) Feedback Inhibitionmentioning
confidence: 94%
“…Therefore, we next investigated how 3 d of MD affects thalamocortical synapse size and density using quantitative immuno-EM. We used the vesicular glutamate transporter (VGluT2) antibody to specifically label thalamocortical terminals in the mouse (Nahmani and Erisir, 2005;Coleman et al, 2010). This approach allows separate analysis of presynaptic input that originates from the LGN and other (mostly intracortical) sources (Fig.…”
Section: Ko Micementioning
confidence: 99%
“…It has been established that functional deprived-eye depression in layer 4 (L4) is mediated by NMDA receptor (NMDAR)-dependent AMPA receptor (AMPAR) internalization (for review, see Cooke and Bear, 2014). Additionally, there are well known anatomical changes in geniculocortical axons and synapses after MD (Hubel et al, 1977;Shatz and Stryker, 1978;Friedlander et al, 1991;Antonini and Stryker, 1993;Antonini et al, 1999). Quantitative immunoelectron microscopy (immuno-EM) in the mouse binocular visual cortex demonstrates that structural effects of MD can occur as rapidly as the functional, electrophysiologically measured effects (Coleman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has detailed further dynamics of ODP, showing that in addition to Hebbian deprived-eye response depression, prolonged MD leads to a second Hebbian phase of potentiation in responsiveness to the non-deprived eye [23,33]. For a more comprehensive review on Hebbian plasticity in the primary visual cortex, please see Cooke & Bear [39].…”
Section: Circuit Mechanisms: Competition Model and Beyondmentioning
confidence: 99%